Production of green liquid soap: an initiative to articulate the principles of Green Chemistry in Natural Sciences teaching (Research, Society and Development, 2022)
Considering the importance of activities that integrate soap production, residual grease and the relations with environmental issues and scientific concepts of Chemistry and Biology, a “green” protocol for ecological liquid soap production is presented, which allows exploring the 12 principles of Green Chemistry as a way of enabling its integration in the teaching and learning process of Natural Sciences. In this sense, it is recommended to consider important requirements to think about theoretical-practical activities in this perspective: to highlight the physical, environmental and health risks of the reagents and products involved in the manufacture of soaps and to determine the residual fat saponification index to avoid excess of caustic soda. Still, the evaluation of the chemical greenness of the procedure is guided according to Green Chemistry holistic metrics and the mass metrics. Finally, a proposal for articulation of Green Chemistry in Basic Education is presented, which can be developed through the three pedagogical moments methodology. In general, the practical actions presented in this article reinforce the importance of critical thinking around the theme Green Chemistry and sustainability articulated to the Teaching of Natural Sciences.